Association between the severity of histopathological lesions and Mycobacterium avium subspecies paratuberculosis (MAP) molecular diversity in cattle in southern Chile - Verdugo, Cristobal; Marquez, Diego; Paredes, Enrique; Moroni, Manuel; Navarrete-Talloni, María José; Tomckowiack, Camilo; Salgado, Miguel (Frontiers in Veterinary Science, 2023)
The objective was to evaluate the association between the severity of histopathological lesions, due to Mycobacterium avium subspecies paratuberculosis (MAP) infection, and the molecular diversity of this pathogen. Blood, ileum, and mesenteric lymph node samples were collected at slaughter, from 1,352 adult cattle (source population 1 (SP1)). Additionally, 42 dairy herds (n=4,963 cows) were followed for two years, and samples from compatible paratuberculosis clinical cases (source population 2 (SP2)) were collected. MAP infection was confirmed by the sequential use of ELISA test, culture in liquid media, and PCR. Isolates were genotyped using five MIRU-VNTR markers. Tissues from confirmed samples were subjected to a histopathological examination. A histopathological severity score (HSS) system was developed and used to grade (0 to 5) the magnitude of lesions caused by MAP. In general, the HSS system assesses the number of foci and degree of macrophage infiltration, together with the presence of multinucleated giant cells (MGC) and acid-fast bacilli (AFB), in addition to fusion of the intestinal villi and hyperplasia of the crypts. Despite the large sampling effort, only 79 MAP isolates were successfully genotyped, where 19 different haplotypes were described. A mixed effect Poisson regression model was used to assess the relation between haplotypes and HSS values. The model was controlled by animal age, and farm was used as random effect. Haplotypes were grouped based on their relative frequency, on most frequent haplotype (group i, 49.4%), second most frequent haplotype (group ii, 12.7%), and all other haplotypes (group iii, 37.9%). Model outputs indicated that group i had significant higher HSS values than group iii. Additionally, the group i was also associated with higher optical density (OD) values of the ELISA test. These results support the existence of differences in pathogenicity between MAP haplotypes. However, results were based on a relatively small sample size, thus these should be taken with caution. Despite this, study findings suggest that haplotypes would be associated with differences in disease progression, where the dominant haplotype tends to generate more severe lesions, which could be linked to a greater shed of MAP cells than non-dominant haplotypes, increasing their chances of transmission.